Better than antibiotics. Public understandings of risk, human health and the use of synthetically obtained livestock vaccines in five European countries. (18th August 2021) - Ditlevsen, Kia; Glerup, Cecilie; Sandøe, Peter; Lassen, Jesper
Abstract : Drawing upon data collected within 20 focus groups with consumers from five European countries, in this article we investigate how perceptions of human health risk and current anxieties regarding agricultural food production affect citizens' acceptance of the use of an emerging biotechnology, synthetic biology, in the development of vaccines for animals bred for food production. In focus group discussions in Austria, the UK, Poland and Denmark, participants tended to value the positive potential of synthetic vaccines if they could solve existing problems. Participants argued that the technology could be beneficial for animal welfare and was a potential solution to the problem of risks to human health posed by the use of antibiotics on livestock. The perceived drawbacks of antibiotic use affected the discussions towards acceptance of synthetic biology and the use of vaccines in meat production despite concerns over the potential risks. The participants from Spain stood out in that their acceptance of the synthetic vaccine appeared to be disconnected from concerns about risks related to the use of antibiotics. Participants from all countries found the vaccine to have potential uses, but also expressed concerns about health risks for consumers. In general consumers were perceived as those bearing the heaviest burden of risk, while pharmaceutical companies were perceived as likely to benefit most from production of the vaccine. We found that institutional trust and national contexts of (dis)engagement with science influenced the participants' understandings of the degree to which the synthetic livestock vaccine had a fair risk-benefit balance.